A use-wear analysis of wood technology of patagonian hunter–gatherers. The case of Cerro Casa de Piedra 7, Argentina. (May 2015) - Caruso Fermé, L.; Clemente, I.; Civalero, M.T.
Abstract: In the Patagonian archaeological record, the preservation of wooden artefacts is very restricted. Functional analysis of lithic artefacts is a way to get a better understanding about the use and consumption of the wood. Technological and use-wear analyses are applied in order to reconstruct the production processes of the wooden artefacts, from the raw-material supplying to the production of the finished tools. In this paper we present the results of a taxonomical and techno-functional analysis of the traces preserved on the surface of the two wooden artefact retrieved from layer 17 (9390 ± 40 C14 years BP) and layer 6 (5310 ± 110 BP) at the site of Cerro Casa de Piedra 7 (province of Santa Cruz, Patagonia, Argentina). The interpretation of these two objects is complicated due to the absence of ethnographical references and the lack of similar archaeological findings in Patagonian hunter–gatherers sites. However, through the observation of the use-wear traces it is possible to reconstruct part of the manufacturing process and advance hypothesis on their mode of employment. Due to the distribution of the wears and the mineral-organic residues identified on the surfaces, it is proposed that one of the wooden artefact was probably used for rock-art production. Highlights: Wood technology of Patagonian hunter–gatherers. Botanical identification. Morphological analysis. Tracing analysis. The analysis of traces preserved on the surface of a wooden artefact.